Strengthening social regulation in the digital economy: comparative findings from the ICT industry. (2nd January 2023) - Doellgast, Virginia
ABSTRACT: National economies with different industrial relations and welfare state traditions are experiencing a similar digital transformation. This article examines how labour unions are seeking to influence digital strategies and investments in the information and communication technology (ICT) industry, based on initial research findings in the US and Germany. These efforts can be divided into three action fields: campaigns focused on influencing state investment and data protection or AI regulation; efforts to extend legal or negotiated labour market protections to new groups of workers; and collective negotiations over new technologies at firm and workplace levels. All three can be seen as complementary in establishing the conditions for the social regulation of new digitally enabled markets.